Connectedness of the African Equity Markets: A Time-Frequency Spillover Analysis - Claassen, Cecily (School of Economics, 2020)
This paper analyses return and volatility spillovers across the five largest and oldest African equity markets, namely: South Africa, Morocco, Egypt, Nigeria and Tunisia. The time-domain approach of Diebold and Yilmaz (2012) and the frequency-domain approach of Barunik and Khrehlik (2018) are employed to measure the spillovers empirically, in order to ascertain the nature and degree of interdependence within African stock markets. The findings suggest that these African equity markets’ total return connectedness index is relatively moderate at an average of 9.7% over the full sample period between 11 January 2002 and 2 November 2018. However, the total volatility connectedness index is much higher at 19.9% on average, which is also larger than many other findings in the literature. These results suggest that South Africa and Egypt are usually the net transmitters of both return and volatility spillovers, while Morocco, Nigeria and Tunisia are usually the net receivers of these spillovers. A subsequent rolling window analysis is then used to show that both return and volatility interconnectivity has increased over time. There are also a number of spikes that occurred during periods of crisis, as these measures are particularly high during the global financial crisis of 2008 and 2009. To consider the robustness of these results, various different frequency windows have been used, where it is noted that although the central tenant of the above findings are present across all frequency windows, the exact measure for the degree of African equity market connectedness is contingent on the frequency under consideration.